Decision Support System For Selection Of Internet Service Provider (ISP) With Analytical Hierarchy Process (AHP) And Simple Additive Weighting (SAW) Methods: Sistem Pendukung Keputusan Pemilihan Penyedia Layanan Internet (ISP) Dengan Metode Analytical Hierarchy Process (AHP) Dan Simple Additive Weighting (SAW) - Anita Diana; Muhamad Ajie Panca Kurniawan (Universitas Singaperbangsa Karawang, 2022)
The use of an internet connection in a company such as a hotel is an important part. As the need for internet services increases, hotels must choose an Internet Service Provider (ISP) vendor according to their needs. This research takes a case study at a 4-star hotel in South Jakarta. The process of selecting ISP vendors is still carried out conventionally and the determination of vendors is appointed directly by Corporate Digital and IT Managers, thus experiencing several obstacles. Among them, the assessment is done subjectively so that the results of the decision are less objective. In addition, it does not yet have a weighted value on the criteria used, so it is not clear which criteria are more important than other criteria. Then, there is no Decision Support System (DSS) application, so there is no recommendation for the selected vendor. Therefore, researchers tried to make DSS in order to create a more objective and effective decision. Some of the criteria set are Bandwidth, Price, List of clients, Customer and Technical Support, and Additional Services determined by the Digital and IT Division at the Hotel. The method used is the Analytical Hierarchy Process (AHP) method to calculate the weight value of the criteria, apnd tested with Software Expert Choice 11, and the SAW method is used to determine the priority ranking of the selected alternative vendors, with varied criteria trends along with the benefit and cost criteria categories. . This study resulted in an application of ISP vendor selection DSS by providing recommendations for selected vendors with the right method. Through the SPK application for selecting ISP vendors by applying the AHP and SAW methods which provide recommendations for selected vendors, it can assist decision makers in determining ISP vendors objectively and effectively according to their needs